An Overview of AI Applications in Cybersecurity for IT Management - Adhikari, Dipak; Thapaliya, Suman (NPRC Journal of Multidisciplinary Research, 2024)
Background: Cybersecurity serves as a defense mechanism against unauthorized access, theft, information disclosure, and service disruptions for electronic data, networks, and computer systems. Traditional cybersecurity strategies have struggled to counter increasingly sophisticated and automated cyberattacks, necessitating the exploration of advanced solutions such as artificial intelligence (AI). Aim: This research aims to highlight the role of AI technology and systems in enhancing cybersecurity measures, addressing how AI-based solutions can defend against cyber threats and identifying the associated challenges and future research directions. Methodology: A systematic literature review was conducted, focusing on recent advancements in AI applications for cybersecurity. Key databases and search engines were utilized to gather relevant articles, which were then filtered based on criteria such as language, publication quality, citation count, and accessibility. The collected literature was analyzed to extract insights on AI methods and their uses in cybersecurity. Results: The study found that AI offers several benefits in addressing cybersecurity concerns. AI systems can identify novel and complex cyber threats, handle substantial volumes of security data, and establish baselines for normal network behavior to detect deviations. Various AI techniques, including neural networks, expert systems, intelligent agents, and machine learning, were identified as effective tools in combating cyber threats. AI has demonstrated significant improvements in the detection and prevention of cyberattacks, enhancing overall cybersecurity effectiveness. Findings: While AI enhances cybersecurity capabilities, it also introduces new challenges such as the need for substantial data and resources, managing false alarms, and vulnerability to adversarial attacks. The study underscores the importance of continuous research to develop robust AI systems that can adapt to evolving cyber threats. Future research should focus on addressing the limitations of AI in cybersecurity, including adversarial threats, data integrity, and human-machine collaboration.